Functional ingredients and innovative dairy products: Scientific and technological review - Víquez-Barrantes, Diana; Cornejo-Gómez, Diana Cristina; Incer-González, Ana Isabel; Cortés-Muñoz, Marianela (Agronomía Mesoamericana, 2024)
Introduction. Understanding consumer behavior in the dairy sector is essential for enhancing competitiveness and defining strategies to meet their requirements and needs. Reviewing scientific information and patents allows for the identification of trends in the addition of functional compounds to dairy products, serving as a critical input for innovation in the food industry. Objective. To identify and analyze trends in the incorporation of functional compounds in dairy products by integrating perspectives from scientific articles and patent analyses. Development. Reviews of both sources revelated a greater application of functional ingredients in yogurt, which opens opportunities for implementation and research in other fermented products such as skyr. Scientific articles indicates an increasing focus on incorporating functional ingredients from unconventional sources into yogurt, ice cream, and cheese. Notable trends include the addition of antioxidants, and proteins, fat reduction, and the substitution of additives. Patents show a tendency toward the incorporation of nutrients, with protein addition being a recurring feature, as well as the inclusion of probiotics, minerals, and antioxidants. Another frequent trend in patents is the optimization of production processes to achieve clean labeling and improve sensory characteristics. The development of dairy products for specific populations is an emerging trend evidenced in the documented strategies. Conclusions. Key trends identified in the dairy industry include an emphasis on fermented products such as yogurt, improved production efficiency, and the addition of functional nutrients aligned with consumer requirements. Both sources highlighted the addition of proteins and antioxidants. An emerging trend identified in the analysis is personalized nutrition, which focuses on using functional nutrients tailored to specific populations groups.